The effect of a comprehensive intervention on anthropometric indices, dietary intake, and physical activity of adolescent boys with overweight - Fatemeh Sadat Hashemi Javaheri; Zahra Mousavi; Saeideh Mohammadi; Arezoo Amjadi; Khadijeh Abbasi Mobarakeh; Seyedeh Hayedeh Mousavi Shalmani; Mahdieh Torkaman; Masoomeh Alsadat Mirshafaei; Sara Khoshdooz; Zahra Saeedirad; Naser Kalantari; Parmis Mirzaei; et al. (BMC Pediatrics)
Abstract Background Non-communicable diseases in adulthood are reported to be strongly associated with adolescent obesity. The present study aimed to assess the effect of a comprehensive lifestyle modification intervention on the anthropometric indices, dietary intake, and physical activity of adolescent boys with overweight. Methods This pragmatic trial was conducted on 126 adolescent boys with overweight. A comprehensive school-based intervention was carried out at two levels for four months: at the school level based on the Ottawa Charter framework and at the personal level including individualized diet and physical activity. Results The percentage of mean difference of BMI and BF loss in the intervention group were 1.20% (P < 0.05) and 6.41% (P < 0.01), respectively. The intervention group had a lower intake of calorie (2350 ± 861 vs. 2634 ± 917 kcal/d), carbohydrate (255.68 ± 41 vs. 286.97 + 47 g/d), and fat (112.67 ± 78 vs. 217.72 ± 86 g/d) after the intervention compared to the control group (All P < 0.05). The intervention resulted in a significant increase in physical activity parameters including distance (3501 ± 287 vs. 614 ± 56 m/d), duration (203 ± 35 vs. 72 ± 10 min/d), and calorie expenditure (359.24 ± 62.4 vs. 46.74 ± 7.5 kcal/d) in the intervention group compared to the control group (P < 0.01). Conclusion A comprehensive lifestyle modification intervention which covers both school and individual levels may positively influence BMI, body fat, calorie intake, and distance and duration of physical activity in adolescents. Thus, adopting multifaceted strategies using the Ottawa Charter framework may be considered as an effective approach to managing obesity in adolescents.